CONSTRUCTION AND GEOGRAPHIC SETTING OF SPATIAL DATA OF DRINKING WATER SUPPLY AND SANITATION –AYA, IN COSTA RICA - González-Ramírez, Esteban Alberto (2016)
The document presents the process and results of the project “Construction and Geographical Setting of Spatial Data of Drinking Water and Sanitation Systems of the Costa Rican Institute of Aqueducts and Sewers” performed by using Geographic Information Systems. It also presents details on how to organize territorial information regarding water and sewer infrastructure, as well as the methods used in the construction and spatial setting of the data that belong to intermediate and rural (peripheral) cities in Costa Rica. Furthermore, it presents the results obtained from the project, and their use in different technical and operational fields.